Selective Extraction of Americium from Curium and the Lanthanides by the Lipophilic Ligand CyMe4BTPhen Dissolved in Aliquat-336 Nitrate Ionic Liquid. Issue 2 (23rd February 2020) - Zsabka, Peter; Hecke, Karen Van; Wilden, Andreas; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
ABSTRACT: The feasibility of separating americium from curium and the lanthanides was studied in batch solvent extraction experiments using an organic solvent composed of 0.01 mol L −1 2, 9-bis(5, 5, 8, 8-tetramethyl-5, 6, 7, 8-tetrahydro-1, 2, 4-benzotriazin-3-yl)-1, 10-phenanthroline (CyMe4 BTPhen) in the ionic liquid Aliquat-336 nitrate [A336][NO3 ] from feed solutions containing N, N, N', N' -tetraethyl diglycolamide (TEDGA), stable lanthanide ions and tracers of 241 Am, 244 Cm, and 152 Eu. The combined use of a lipophilic and a hydrophilic ligand with opposite selectivity for Am(III) vs. Cm(III) and Ln(III) allowed the separation of Am(III) from Cm(III) and Ln(III) from moderate acidic feed solutions (1 mol L −1 HNO3, SF Am/Cm = 3.1–3.9, SF Am/La > 75, SF Am/Eu ≥ 3000).